1973
DOI: 10.1159/000224848
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria and Lymphoreticular Tumours in <i>Xenopus laevis, </i>the South African Clawed Toad

Abstract: Lymphoreticular tumours, mycobacterial granulomata and responses to antigens in Xenopus toadlets were compared. Lymphoreticular tumours and granulomata differed in histology, development, distribution of mitotic figures, involvement of small lymphocytes, aetiology and transmissibility. Combination experiments provided no evidence that Mycobacterium marinum plays a role in lymphoreticular tumour initiation and development, though, as in some human neoplasms, secondary mycobacterial infection was a feature of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Clothier & Balls also showed that low doses of live M. marinum injected into healthy xenopus toadlets caused an increase in the number of small lymphocytes in the lymphoid tissues (spleen, liver and kidney), whilst high doses induced granulomata. Cell cultures from mycobacteriuminfected tissues revealed large numbers of macrophages, and their concentration in the lymph was found to be much greater in infected toads than in uninfected animals (Clothier 1972 There is no evidence in either urodeles or anurans for a secretory antibody structurally comparable with mammalian IgA, although few serious attempts have been made to look for it. Jurd (1977) has recently reported that antibodies in the bile and gut secretions of xenopus resembled circulating antibody in their structure, and he could find no immunoglobulin in the mucus of the skin.…”
Section: Phagocytosismentioning
confidence: 99%
“…Clothier & Balls also showed that low doses of live M. marinum injected into healthy xenopus toadlets caused an increase in the number of small lymphocytes in the lymphoid tissues (spleen, liver and kidney), whilst high doses induced granulomata. Cell cultures from mycobacteriuminfected tissues revealed large numbers of macrophages, and their concentration in the lymph was found to be much greater in infected toads than in uninfected animals (Clothier 1972 There is no evidence in either urodeles or anurans for a secretory antibody structurally comparable with mammalian IgA, although few serious attempts have been made to look for it. Jurd (1977) has recently reported that antibodies in the bile and gut secretions of xenopus resembled circulating antibody in their structure, and he could find no immunoglobulin in the mucus of the skin.…”
Section: Phagocytosismentioning
confidence: 99%
“…Thus, while injections of large doses of the bacteria alone induce lesions distinguishable from the lymphoreticular neoplasm, the bacteria could still play a role in the development of the tumour. Further ex periments designed to investigate this possibility are discussed in the follow ing article [8],…”
Section: Discussionmentioning
confidence: 99%
“…We have divided the bacterial response into three main stages -BR1, BR2, BR3 [see also 8]. In BR1, the cortical zone of the liver showed a general thickening, mainly due to an increase in the number of lymphoid stem cells and histiocytes.…”
Section: Histological Development O F Lesions Induced By Isolated Mycmentioning
confidence: 99%
“…We subsequently studied lymphoreticular tumours and mycobacterial granulomata in Xenopus [14,15] and found that the two diseases differed in histology, development, distribution of cells in the S-phase and M-phase of the cell cycle, aetiology, and transmissibility. We considered involve ment of mycobacteria in some Xenopus tumours to be a secondary result rather than a primary cause of tumor development.…”
Section: Classification O F Amphibian Tumoursmentioning
confidence: 99%